IPTEKS PROSES PELAKSANAAN PASAR LELANG DINAS PERINDUSTRIAN DAN PERDAGANGAN DAERAH DAERAH PROVINSI SULAWESI UTARA - Siallagan, Bernita; Tirayoh, Victorina Z. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Auction market is trading system in which buyers compete with other buyers and sellers compete with other sellers to reach the most favorable prices at the same place. The auction market is one of the effective ways in the trading system through transparency in pricing mechanisms, increasing incentives for increased production and quality. This auction market is also able to help cut long chains. With the government auction market facilitating sellers / farmers (producers) and buyers (consumers) to meet in one place without an intermediary (distributor) so as to streamline the trade chain. To improve the quality of the auction market, an analysis of the process of conducting the auction market is needed from the department of Industry and commerce of North Sulawesi area. By analyzing auction market implementation process carried out by the North Sulawesi Provincial Office of Industry and Commerce in accordance with the Decree of the Minister of Industry and commerce of the Republic of Indonesia No.650 of 2004.Keyword : implementation, effective, auction market, process